Analisis Cara Belajar Siswa Berprestasi Kelas IV Di SDN 097376 Sippan - Sinurat, Rensister; Tanjung, Darinda Sofia; Anzelina, Dewi; Abi, Antonius Remigius (Jurnal PGSD, 2021)
This study aims to determine the learning methods of the fourth grade students of SDN 097376 SIPPAN. The form of this researchis descriptive qualitative research. The subjects in this study were grade IV SDN 097376 SIPPAN. Data collection techniques in this study are observation techniques, interview techniques and documentation techniques. Based on the results of the study, it can be concluded that the way of achieving student learning is discipline of learning every night at home, repeating lessons at home for 1 hour and being able to discuss it again in the morning, reading and making interesting summaries of the subject matter so that it is easy to learn again, practice answering questions practice questions to deepen understanding, follow school lesson swell. Actively asking the teacher, practice concentration in following lessons.